Concept-formation and deep disagreements in theoretical and practical reasoning. - Wee, Michael (Synthese, 2025)
This paper explores the idea that deep disagreements essentially involve disputes about what counts as good reasoning, whether it is theoretical or practical reasoning. My central claim is that deep disagreements involve radically different paradigms of some principle or notion that is constitutively basic to reasoning—I refer to these as “basic concepts”. To defend this claim, I show how we can understand deep disagreements by accepting the indeterminacy of concept-formation: concepts are not set in stone but are responsive to human needs, and differences in individuating and ordering concepts lead to clashes in paradigms of reasoning. These clashes can be difficult to resolve because linguistic concepts, especially basic concepts, impose a normative structure onto thought to make reasoning possible at all. This, I also argue, is an authentically Wittgensteinian account of the nature of reasoning. While deep disagreements involving theoretical and practical reasoning both stem from the same root problem of clashing paradigms of basic concepts, I will also draw attention to the particularly radical indeterminacy of moral concept-formation, which makes moral deep disagreements more difficult to resolve. Over the course of the paper, I will discuss two examples of deep disagreements to illustrate and defend my central claim: deep disagreements over vaccines and the concept of “evidence” (theoretical reasoning) and deep disagreements over affirmative action and the concept of “fairness” (practical reasoning). I conclude by suggesting how my account of reasoning does not lead to moral relativism.